Lipids of Parasitic and Saprophytic Leptospires - Johnson, R. C. (1970)
The lipid composition of five parasitic and six saprophytic leptospires was compared. Lipids comprise 18 to 26% of the dry weight of the cells after chloroform-methanol extraction. No residual (bound) lipid was found after acid or alkaline hydrolysis of the extracted residue. The total lipid was composed of 60 to 70% phospholipid, and the remaining lipid was free fatty acids. The phospholipid fraction contained phosphatidylethanolamine as the major component, and phosphatidylglycerol and diphosphatidylglycerol were minor components with traces of lysophatidylethanolamine sometimes found. The major fatty acids of leptospires were hexadecanoic, hexadecenoic, and octadecenoic acids. Both the unusual cis-11-hexadecenoic acid and the more common cis-9-hexadecenoic acid were synthesized by the leptospires. Neither the parasitic nor the saprophytic leptospires can chain elongate fatty acids. However, they were capable of β-oxidation of fatty acids. Both groups of leptospires desaturate fatty acids by an aerobic pathway. When the parasite canicola was cultivated on octadecanoic acid, 87% of the hexadecenoic acid was the 11 isomer, whereas the saprophyte semeranga consisted of 10% of this isomer. In addition, the saprophytic leptospires contained more tetradecanoic acid than the parasites. No differences were observed in the lipid composition of virulent and avirulent strains of canicola.